Pengaruh Work Life Balance Dan Reward Terhadap Kepuasaan Kerja Pada PT. Andalas Dolomit Sejahtera - Yulan Mardiansyah; Rita Srihasnita Rosali Caniago (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to examine the influence of work-life balance and rewards on job satisfaction at PT. Andalas Dolomit Sejahtera. This study used quantitative methods, collecting data through questionnaires distributed to 60 student respondents.Based on the research results and data analysis using SPSS (Statistical Product and Service Solutions), it shows that: (1) Work-life balance has a positive and significant influence on job satisfaction, (2) rewards have a positive and significant influence on job satisfaction, (3) both work-life balance and rewards have a positive and significant influence on job satisfaction. Simultaneously, these two independent variables have a significant influence on job satisfaction.